Local Wisdom in Language Learning: The Role of Translated Langsa Folklore in Improving Students’ English Competence - Chairuddin, Chairuddin; Mukminin, Amirul; Barus, Efendi; Nuzwaty, Nuzwaty (International Journal of English and Applied Linguistics (IJEAL), 2025)
This study aims to analyze the effectiveness of using Langsa City folklore, translated from Indonesian into English, in enhancing children’s English learning outcomes. The research background stems from students’ low motivation and limited English proficiency, as well as the need for contextual and culturally relevant learning media. The study employed a quasi-experimental design involving two groups: the experimental group (n=30), which received instruction using translated folklore, and the control group (n=30), which followed conventional learning methods. Data were collected through pre- and post-tests of English competence, learning motivation questionnaires, and interviews with teachers and students. The findings indicate a significant improvement in the experimental group compared to the control group, both in English proficiency (p < 0.001) and learning motivation (? = +0.9). Qualitative analysis revealed that students were more enthusiastic and engaged with the material due to its familiar cultural values. The main challenges included limited time and difficulty in translating certain cultural vocabulary directly. Overall, the study concludes that translated Langsa folklore is an effective medium to enhance students’ learning outcomes and motivation in English language education. The implications emphasize the importance of developing local wisdom-based teaching materials to support foreign language learning in secondary schools.